Study on Factors Affecting Households’ Income Generation from Natural Dyed Cotton Handicaft Production in Songkhone District, Savannakhet Province: https://doi.org/10.69692/SUJMRD080278 - TOUNMANYSONE, Thongsa; BANMANIVONG, Lidsada; VONGKEO, Somphone; XAIYAPHONE, Bounpasong; SENGHEUANGSOMPHOU, Douangpheng; LATSAVAT , Soulang; MONEPADITH, Soksay (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this study was to find out the factors that affect households’ income generation from natural dyed cotton handicraft (NDCH) production in Songkhone District, Savannakhet Province. The researcher used cross-sectional data collected from a sample of 256 households in Songkhone district, Savannakhet province in 2021. The estimates are based on the regression model (Ordinary Least Square: OLS) and the econometrics analysis is based on the model constructed by Souphaphone (2020). The results of this study showed that NDCH production can generate households’ income at an average of 6.992.109 kip/household/month and the factors that have an effect on households’ income generation from NDCH production (statistically significant) have 5 factors, including experience, labour, market, and Laoskirt (Sinh) have positive impact on household’s income generation. But training has a negative impact on a household’s income generation. Therefore, policymakers should recognize that NDCH production can generate households’ income and also have a significant impact on the strategy of creating jobs and promoting Lao culture. This study is an important case study to explore the factors affecting households’ income generation from NDCH production in Savannakhet, Lao PDR.